Factores asociados con infección de herida quirúrgica en cirugía general. Hospital José María Velasco Ibarra, 2020 -2021 - Caiza Eugenio, Vanessa Maribel (2021)
ABSTRACT: Introduction: Surgical site infections (SSI) are considered the third most frequent infection of intrahospital origin with 16% and the first in patients undergoing surgery; at the level of Latin America, the incidence is 4.12%; in Ecuador, in 2016, an incidence of 0.97% was shown. Objective: The primary purpose of the research is to identify the risk factors that predispose to surgical wound infection in patients treated in the Surgery service of the José María Velasco Ibarra Hospital, period September 2020 - August 2021. Methodology: This work corresponds to a descriptive, observational, cross-sectional, retrospective study. The information will be synthesized through the data matrix, taking 260 patients as a sample. Results: 8 patients presented SSI with a prevalence of 3.08%, four were male and four female, the dirty wound prevailed in 5 patients approached by conventional surgery, 4 of them were placed drainage, two were re-operated, who recorded the most extended length of hospital stay, 6 and 14 days. Most of the cases presented type II diabetes mellitus associated with obesity and hypertension. Conclusions: We emphasize the statistically significant association as a protective factor between prophylactic and postsurgical treatment, laparoscopic approach, and postoperative control, and statistically significant association for the type of wound, approach by conventional surgery, use of drainage, consequences of hospital stay. Keywords: Surgical site infection, risk factors, surgery.